Poly(ionic liquid)/Ce‐Based Antimicrobial Nanofibrous Membrane for Blocking Drug‐Resistance Dissemination from MRSA‐Infected Wounds. (31st March 2021) - Luo, Zhenhong; Cui, Hengqing; Guo, Jiangna; Yao, Jieran; Fang, Xia; Yan, Feng; Wang, Bin; Mao, Hailei
Abstract: Resistant bacteria have become a global threat. Even if bacteria are killed, their carried drug‐resistant genes can remain in the environment and spread to other microbes via horizontal gene transfer. Development of antimicrobial materials with intrinsic gene break down activity can prevent the dissemination of released drug‐resistant genes from the dead bacteria. Herein, imidazolium type poly(ionic liquid) (PIL)/cerium (IV) ion‐based electrospun nanofibrous membranes (PIL‐Ce) are synthesized. The effects of PIL and Ce moieties on the antimicrobial properties against Gram‐negative Escherichia coli and kanamycin‐resistant E. coli, and Gram‐positive Staphylococcus aureus and methicillin‐resistant S. aureus (MRSA), as well as deoxyribonuclease‐mimic activities to the drug‐resistant genes of Kan R ( E. coli ) and mecA (MRSA) are investigated. The Ce‐containing PIL membranes show the high efficiencies to eradicate bacteria and disintegrate drug‐resistant genes. A wound treatment test using MRSA infected mice as the model further demonstrate that PIL‐Ce membranes combine both antibacterial and DNase‐mimic properties, and may have the potential application as a new "green" wound dressing to block the drug resistance spread in a clinical setting. Abstract : Dual‐functional membranes with both antibacterial and deoxyribonuclease‐mimic properties are synthesized in this work. The prepared poly(ionic liquid)/cerium ion‐based electrospun nanofibrous membranes can not only kill the drug‐resistant strains but also prevent the dissemination of antibiotics resistance genes released from the dead bacteria, and may have potential application as a new "green" wound dressing in a clinical setting.